Potential of a Public Information Commission Based on Public Information Disclosure Principles to Improve State Public - Setyawan, Bambang (Universitas Airlangga, 2021)
The free flow of information and ideas is essential for democracy and respect of human rights. Censorship has the potential to allow human rights violations to occur in secret, hinder investigations into corrupt and inefficient governments, and many other things. Based on this background, this research is a legal study that takes a statutory, conceptional, and case approach to examine the following issues: 1) the philosophical basis of public bodies as public institutions providing information in the era of public information openness; 2) the existence of an information commission as an administrator and law enforcer in public information disclosure; and 3) public entities' liability against disputes based on public information from the aspects of administrative, civil, and criminal law. We conclude that freedom of information is in the spirit of democratisation that ensures freedom, based on which the state can function effectively and efficiently without neglecting democratic principles. The enactment of the UU KIP in Indonesia on 30 April 2010 opened a new era of public information disclosure in the country. This law is part of the desire to implement a spirit of transparency to fulfil citizens' human right to access public information (right to know) guaranteed by Art. 28F of the 1945 Constitution of the Republic of Indonesia.